DISKRESI KEPOLISIAN DALAM PENYELESAIAN PERKARA PIDANA BERBASIS KEARIFAN LOKAL - Desi Apriani; Heni Susanti (Fakultas Hukum Universitas Riau, 2018)
The purpose of writing this article is to explain the discretion of the police in the settlement of criminal cases based on local wisdom. This study uses an empirical method, by conducting interviews. Law enforcement in post-colonial Indonesia becomes formal and rigid and bureaucratic. Justice is as if it can only be obtained in an institution called court, so that in many cases the judicial process continues even though the parties have personally made peace. Police discretion as permitted by Police law is the most ideal step or way to change the rigidity of law enforcement. Certainly the discretion referred to here must be accountable on the basis of common interests, humanity and justice. This needs to be done in order to move the law into an Indonesian context based on local wisdom.